Subjugating Female Voice in Nobokov’s Lolita - Niroula, Youba R. (CMC Journal, 2026)
Vladimir Nabokov’s Lolita, often criticized for its controversial themes, offers a critical perspective on the ways in which patriarchal social norms perpetuate gender inequality and constrain women’s agency. This qualitative study examines the concept of “manterruption”, the practice of men interrupting or dominating women in discourse; through first-wave feminist literary criticism, it becomes clear that the work is expressing the unequal power relations between men and women that exist in the wider world. Focusing on Humbert Humbert's narrative dominance and his interactions with female characters, the analysis explores how patriarchal authority is constructed and sustained within the novel. Using secondary sources, the study investigates themes of female subjugation, objectification, and gendered communication patterns, situating the text within its social and cultural contexts. The findings reveal that Lolita reflects systemic oppression embedded in patriarchal structures while simultaneously exposing the mechanisms through which male authority marginalizes female voices. By foregrounding issues of power, discourse, and gender inequality, the study underscores the importance of challenging traditional gender roles and advocating for women’s agency as represented in literary narratives. Thus, the novel is a manifestation of the unfulfilled desire of an adult man towards the girl for his personal pleasure, i. e., sexual object as in the first wave of feminism.